Splines in convex sets under constraints of two‐sided inequality type in a hyperplane - Asmuss, Svetlana (Mathematical Modelling and Analysis, 2008)
The problem of minimization of a smoothing functional under inequality constraints is considered in a hyperplane. The conditions of the existence of a solution are obtained and some properties of this solution are investigated. It is proved that the solution is a spline. The method for its construction is suggested. First Published Online: 14 Oct 2010